Optimal Antiretroviral Prophylaxis in Infants at High Risk of Acquiring HIV: A Systematic Review. Issue 2 (February 2018) - Beste, Sara; Essajee, Shaffiq; Siberry, George; Hannaford, Alisse; Dara, Jasmeen; Sugandhi, Nandita; Penazzato, Martina
Abstract : Introduction: The risk of perinatal HIV infection can be dramatically reduced through maternal antiretroviral (ARV) therapy and infant ARV postnatal prophylaxis. The 2013 World Health Organization guidelines recommended 4–6 weeks of nevirapine or zidovudine as postnatal prophylaxis, with possible extension to 12 weeks for high-risk breastfed infants. A systematic review was undertaken to determine if there is evidence for the World Health Organization to recommend enhanced or extended prophylaxis for high-risk infants. Methods: Cochrane CENTRAL, EMBASE, PubMed databases from 2005 to 2015, as well as conference on retroviruses and opportunistic infections and international aids society abstracts were searched. Cohort studies and randomized controlled trials examining the use of combination or prolonged regimens in HIV-exposed infants were included. A total of 1185 studies were screened by title and abstract and 45 full-text articles were examined in further detail. Results and Discussion: Of the 4 included studies, 3 examined multidrug prophylaxis regimens in formula-fed, high-risk HIV-exposed infants. Multidrug regimens were shown to significantly reduce transmission rates, compared with single-drug regimens; however, there was no significant difference between 2- and 3-drug regimens. An randomized controlled trial examining prolonged ARV prophylaxis in a breastfed population showed that 6 months of nevirapine resulted in lower HIV transmission rates compared with a standard 6-week nevirapine regimen. Conclusions: The limited available evidence suggests that using combination ARV regimens in high-risk infants reduces intrapartum transmission and that using prolonged prophylaxis in breastfed infants reduces breastfeeding transmission rates. However, the additional benefit of combination or prolonged regimens in the context of maternal ARV therapy remains unclear. Abstract : Supplemental Digital Content is available in the text.